Identification of polyketide synthase 13 inhibitor: Pharmacophore-based virtual screening and molecular dynamics simulation - Muhammad Arba, Andy-Nur Hidayat, Henny Kasmawati, Yamin Yamin, Ida Usman (Journal of Applied Pharmaceutical Science, 2019)
Polyketide synthase 13 (Pks13) is one of prominent targets to treat Mycobacterium tuberculosis (Mtb). In the present study, pharmacophore features for Pks13, including two hydrogen bond donors, one hydrogen bond acceptor, and one hydrophobic feature, were built using a novel Pks13 inhibitor, TAM16. The pharmacophore features were then used to perform virtual screening on ZINC database to identify small molecules of Pks13 inhibitors. The obtained virtual hits of 107 small molecules were subjected to molecular docking studies employing iDock software to reveal their binding orientation to Pks13. Furthermore, four best hits, each bound to Pks13, were submitted to 40-ns molecular dynamics simulation to explore their conformational changes throughout simulation. The result showed that all hit compounds, i.e., Lig79/ZINC09281113, Lig94/ZINC09584070, Lig95/ZINC09209668, and Lig97/ZINC09216165, have better stabilities than that of TAM16 as indicated by their lower values of root-mean-square-deviation and root-mean-square-fluctuation. In a similar way, prediction of binding free energy using molecular mechanics Poisson– Boltzmann Surface Area method showed that all hit compounds have lower binding free energies than that of TAM16, indicating their potential as novel compounds of Pks13 inhibitors.
Keywords: Polyketide synthase 13, pharmacophore modeling, molecular docking, molecular dynamics simulation.